Evaluating the role of Ayurveda management in Yuvana Pidaka with special reference to Acne vulgaris: A case study - Kumari, S.M.M.W.; Rathnayake, R.L.Y.U. (University of Colombo, 2025)
Acne vulgaris has been one of the most common problems of the young population. It has been described as Shalmali thorn like eruptions on the face due to vitiation of Kapha, Vata and Rakta dosha in Ayurveda. It can be correlated to Yuvana pidaka described under Kshudra roga in Ayurveda. The study was conducted to find out the role of Ayurveda management in Yuvana pidika. The major signs and symptoms were multiple acne with papules and pustule, itching, pain and blackish spots on face. A 16-year-old male patient having multiple acne with papules and pustules, itching, pain and blackish spots on face for the past 3 months presented at the OPD, Ayurveda Hospital Pallekele, Sri Lanka was enrolled in the study and consent was obtained and signs and symptoms were recorded. The investigations were done and data were collected based on available clinical facilities. The treatment regimen included internal medicines such as Vasa guduchi kashaya, Manibadhra choorna, Kaishoora guggulu followed by the Lodhradi lepa and Raktha chandanadhi lepa with Pinda oil application and Pancha walkala pariseka sweda on the face externally for 28 days. Reduction of the signs and symptoms were assessed using The Investigator's Global Assessment (IGA) Scale and Clinical Features Grading System. The patient had relief in all the sign and symptoms after 28 days of treatment with no new eruptions. Excellent improvement in The Investigator's Global Assessment (IGA) Scale was observed from grade 5 to 0. This case study demonstrates the effectiveness of Ayurveda in the management of Yuvana pidaka. In future, clinical trials should be planned with a larger sample size to generalize the findings.
Keywords: Acne vulgaris; Yuvana pidaka; Lepa; Pariseka sweda